The Effect of Academic Stress on Learning Concentration in Mathematics: Evidence from Fifth-Grade Elementary Students - Rizal, Syamsur (Papanda Publisher, 2025)
Academic stress is one of the psychological factors that may influence students’ ability to concentrate during the learning process, particularly in mathematics, which requires a high level of focus. Many elementary school students face academic pressure such as heavy assignments, grade expectations, and continuous evaluations, which negatively affect their learning concentration. This condition poses a serious problem since low concentration directly impacts students’ academic achievement, especially in subjects that demand logical and systematic understanding such as mathematics. This study employed a quantitative approach with a correlational design. The participants were 35 fifth-grade students of Madrasah Ibtidaiyah NW Aikmel, consisting of 19 boys and 16 girls. Data were collected using academic stress questionnaires and learning concentration scales, both of which had been tested for validity and reliability. The data were analyzed using simple linear regression with the assistance of SPSS software. The study was conducted over a six-month period, from July to December 2024. The results revealed a significant negative effect of academic stress on students’ learning concentration. The higher the level of academic stress experienced, the lower the students’ ability to concentrate in learning mathematics. These findings support the theory that psychological factors play an essential role in determining learning quality alongside cognitive ability. In conclusion, academic stress is proven to be an important variable that must be considered in efforts to improve elementary school students’ learning concentration. Therefore, teachers, schools, and parents are expected to manage academic pressure proportionally to ensure that students’ concentration remains optimal.